2008
DOI: 10.1073/pnas.0709189105
|View full text |Cite
|
Sign up to set email alerts
|

Blue light-induced autophosphorylation of phototropin is a primary step for signaling

Abstract: Phototropins are autophosphorylating protein kinases of plantspecific blue light receptors. They regulate various blue light responses, including phototropism, chloroplast movements, hypocotyl growth inhibition, leaf flattening, and stomatal opening. However, the physiological role of autophosphorylation remains unknown. Here, we identified phosphorylation sites of Ser or Thr in the N terminus, Hinge1 region, kinase domain, and C terminus in Arabidopsis phototropin1 (phot1) by liquid chromatographytandem mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
310
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 228 publications
(325 citation statements)
references
References 40 publications
11
310
2
2
Order By: Relevance
“…This demonstrates for the first time that phosphorylation of phot1 is an essential step of signaling [16]. This residue of the kinase-domain activation loop is well conserved among members of the PKA family [4,16]. Phosphorylation of the equivalent site in PKA enhances kinase activity and substrate recognition [4].…”
Section: Phototropin Kinase Activity and Signal Transductionmentioning
confidence: 75%
See 4 more Smart Citations
“…This demonstrates for the first time that phosphorylation of phot1 is an essential step of signaling [16]. This residue of the kinase-domain activation loop is well conserved among members of the PKA family [4,16]. Phosphorylation of the equivalent site in PKA enhances kinase activity and substrate recognition [4].…”
Section: Phototropin Kinase Activity and Signal Transductionmentioning
confidence: 75%
“…Four phosphorylation sites were identified upstream of the LOV2 domain, similar regions of phot1 are phosphorylated in vitro [10]. A second study identified two additional sites in the photosensory domain, and three phosphorylation sites in the kinase domain of phot1 [16] (Figure 1). The characterization of point mutants showed that autophosphorylation of Ser851 (but none of the other residues) is necessary to trigger phototropin-dependent responses [16].…”
Section: Phototropin Kinase Activity and Signal Transductionmentioning
confidence: 91%
See 3 more Smart Citations